Reinforcement Bunchems Play Therapy Supports Attention in ADHD Child: Terapi Bermain Bunchems dengan Penguatan Mendukung Perhatian pada Anak ADHD - Leli Dwi Mita Sakti; Zaki Nur Fahmawati (Academia Open, 2025)
General Background: Attention Deficit Hyperactivity Disorder (ADHD) is characterized by persistent inattention, impulsivity, and hyperactivity that interfere with learning activities and daily functioning. Specific Background: Play therapy using educational game media, such as Bunchems—colored interlocking balls assembled into various shapes—has been proposed as a behavioral modification strategy combined with reinforcement techniques to facilitate attention control in children. Knowledge Gap: Previous studies have explored play therapy for ADHD, yet limited empirical evidence documents reinforcement-based Bunchems play using single subject research designs to examine attention-related behavioral indicators. Aims: This study examined the role of reinforcement-based Bunchems play therapy in supporting attention ability in a child diagnosed with ADHD. Results: Using a quantitative quasi-experimental single subject research with an A–B design, observations were conducted across four baseline sessions and eight intervention sessions involving a six-year-old participant. Baseline findings showed the participant could distinguish only two to three color groups and frequently experienced attention distraction. During the intervention, reinforcement through praise and applause accompanied Bunchems play tasks, resulting in the participant distinguishing up to five color groups and maintaining task completion with fewer distractions, although statistical stability remained variable and changes were not significant. Novelty: This study introduces reinforcement-integrated Bunchems play as a structured behavioral modification approach within a single-subject experimental framework. Implications: The findings indicate Bunchems play therapy combined with reinforcement may serve as an alternative intervention strategy to support attention-related learning processes in children with ADHD, particularly when implemented repeatedly and over extended durations. Highlights: Color-Group Task Performance Increased From Limited Differentiation to Full Grouping Accuracy. Motivational Feedback Maintained Task Completion and Reduced Observable Distraction Behavior. Behavioral Observation Data Demonstrated Variable Yet Observable Upward Performance Trends Across Intervention Sessions. Keywords: ADHD, Bunchems Play Therapy, Reinforcement Technique, Attention Ability, Single Subject Research